Study on Antiinflammatory Effects of Ailanthus altissima Leaves Extract - Huo, Qing; Mei Gu, Xue; Lin, Qiang (Asian Journal of Chemistry, 2011)
This study involves the antiinflammatory effects of Ailanthus altissima leaves extract. The inflammation models of xylene-induced mice ear swelling and foot swelling in mice resulting from 10 % of fresh egg white plus physiological saline solution has been established. Compared with the model groups, the high-dose group of Ailanthus altissima extract could against the foot swelling in mice resulted from 10 % of fresh egg white plus saline well and there had certain antiinflammatory effect on xylene-induced mouse ear swelling, but the result was not so significant. Ailanthus altissima extract had certain antiinflammatory effect.